2020
DOI: 10.3389/fped.2020.00366
|View full text |Cite
|
Sign up to set email alerts
|

Renal Precision Medicine in Neonates and Acute Kidney Injury: How to Convert a Cloud of Creatinine Observations to Support Clinical Decisions

Abstract: Renal precision medicine in neonates is useful to support decision making on pharmacotherapy, signal detection of adverse (drug) events, and individual prediction of short- and long-term prognosis. To estimate kidney function or glomerular filtration rate (GFR), the most commonly measured and readily accessible biomarker is serum creatinine (S cr ). However, there is extensive variability in S cr observations and GFR estimates within the neonatal population, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 65 publications
2
56
0
2
Order By: Relevance
“…Similar to the findings by Go et al [4], we observed a positive correlation of S cr at birth with GA (week, in the absence of data on days) in a large, pooled, and heterogeneous cohort (882 S cr observations, GA range 23–42 weeks) of neonates [4, 6, 7]. Although statistically significant, the clinical impact of this positive correlation is rather limited (24–40 weeks, 54.5–60.2 μmol/L, +10%).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to the findings by Go et al [4], we observed a positive correlation of S cr at birth with GA (week, in the absence of data on days) in a large, pooled, and heterogeneous cohort (882 S cr observations, GA range 23–42 weeks) of neonates [4, 6, 7]. Although statistically significant, the clinical impact of this positive correlation is rather limited (24–40 weeks, 54.5–60.2 μmol/L, +10%).…”
Section: Resultssupporting
confidence: 89%
“… Individual S cr values at birth (Cr birth ) in a pooled dataset in neonates (GA range 23–42 weeks) display a significant correlation (rank correlation) with GA [6, 7]. S cr , serum creatinine; GA, gestational age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, the definition is based on trends (increase) in serum creatinine concentrations and in urine output to result in AKI staging (stage 0-3) ( Table 1). However, as the dynamics in serum creatinine are most pronounced in ELBW neonates with an initial physiological increase up to day 3 and a subsequent progressive decrease over the next weeks, these trends are difficult to capture within a 'fixed or proportional increase to former creatinine observation' approach, and perhaps does not provide the granularity needed to detect 'minor changes' [25].…”
Section: Aminoglycosides and Vancomycin Related Acute Kidney Injurymentioning
confidence: 99%